N‐terminal pro‐B‐type natriuretic peptide and cardiac troponin T in non‐immune hydrops. Issue 4 (20th January 2016) - Lee, Seung Mi; Jun, Jong Kwan; Kim, Su Ah; Kang, Min Ji; Song, Sang Hoon; Lee, JoonHo; Park, Chan‐Wook; Park, Joong Shin
Abstract: Aim: We analyzed the N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and cardiac troponin T (cTnT) in non‐immune hydrops cases, to determine whether congestive heart failure or inadequate cardiac output may be mechanisms underlying abnormal fluid collection in hydrops. Methods: The study population consisted of singleton neonates with non‐immune hydrops and healthy control neonates, matched for both gestational age at delivery and mode of delivery. The subjects were divided into three groups: group 1, hydrops of cardiac origin (n=6); group 2, hydrops of non‐cardiac origin (n=17); and group 3, control (n=23). The NT‐proBNP and cTnT were measured in the cord blood collected at the time of delivery. Results: The median cord blood concentrations of NT‐proBNP and cTnT were not different between the hydrops (groups 1 and 2) or control cases. However, the NT‐proBNP level was elevated in group 1 compared with groups 2 and 3. The concentrations of cTnT did not differ among the three groups. Conclusions: The concentration of NT‐proBNP was only elevated in cases of hydrops of cardiac origin. Congestive heart failure might not be the underlying mechanism of fluid collection in cases of non‐immune hydrops of non‐cardiac origin, and NT‐proBNP may be a promising tool to differentiate the origin of hydrops.